Relationships among yield, girth and some structural characters of the laticiferous system in young seedlings of rubber trees (Hevea) - Souza Goncalves P De; Bortoletto N; Carvalho A Z; Martins A L M (Brazilian Journal of Genetics, 1995)
The relationship between growth, yield and the laticiferous system of Hevea brasiliensis seedlings at the nursery stage was investigated. Thirty seedlings with yield levels ranging from high to low were evaluated for juvenile growth (G), yield (Y) and bark structural characters including: bark thickness (BT), total number of latex vessel rings (LV), overall density of latex vessels per ring per 5 mm2 of bark (DV), average latex vessel diameter (DL) and average distance between consecutive latex vessel rings (AD). There were significant linear correlations between Y and LV or DV. No correlations were detected between Y and G or BT. Correlations between G and BT were positive and significant. Multiple regression studies of Y on DV, LV, DL, BT and G suggested that DV and DL, though non-significant, jointly accounted for 49;of yield variation. When G was the dependent variable, with BT and DV as independent variables, BT was the only important and significant variable, accounting for 39;and 17;of the variation in LV. Girth and bark thickness did not give significant positive predictive power for LV.
Source Year: 1996
Keywords: Girth; Hevea brasiliensis; Laticiferous system; Yield